Class II alpha-mannosidase from aspergillus fischeri: energetics of catalysis and inhibition - Shashidhara, K. S.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2009)
Energetics of the catalysis of Class II alpha-mannosidase (E.C.3.2.1.24) from Aspergillus fischeri was studied. The enzyme showed K(cat)/K(m) for Man (alpha 1-3) Man, Man (alpha 1-2) Man and Man (alpha 1-6) Man as 7488, 5376 and 3690 M(-1) min(-1), respectively. The activation energy, Ea was 15.14, 47.43 and 71.21 kJ/mol for a1-3, alpha 1-2 and alpha 1-6 linked mannobioses, respectively, reflecting the energy barrier in the hydrolysis of latter two substrates. The enzyme showed K(cat)/K(m) as 3.56 x 10(5) and 4.61 x 10(5) M(-1) min(-1) and E(a) as 38.7 and 8.92 kJ/mol, towards pNP alpha Man and 4-MeUmb alpha Man, respectively. Binding of Swainsonine to the enzyme is stronger than that of 1-deoxymannojirimycin. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Mannosidase; Energy of activation; kinetics; Swainsonine

Conformational and functional transitions in class II alpha-mannosidase from aspergillus fischeri - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2010)
The conformational transitions in an oligomeric and high molecular weight class II alpha-mannosidase from Aspergillus fischeri were examined using fluorescence and CD spectroscopy under chemical, thermal and acid denaturing conditions. The enzyme lost the activity first and then the overall folded conformation and secondary structure. The midpoint values of GdnHCl mediated changes measured by inactivation; fluorescence and negative ellipticity were 0.48 M, 1.5 M and 1.9 M, respectively. The protein almost completely unfolded in 4.0 M GdnHCl but not at 90 A degrees C. The inactivation and unfolding were irreversible. At pH 2.0, the protein exhibited molten-globule like intermediate with rearranged secondary and tertiary structures and exposed hydrophobic amino acids on the surface. This species showed increased accessibility of Trp to the quenchers and got denatured with GdnHCl in a different manner. The insoluble aggregates of a thermally denatured protein could be detected only in the presence of 0.25-0.75 M GdnHCl.
Keywords: Aggregation; alpha-Mannosidase; ANS binding; Circular dichroism; fluorescence; GdnHCl; Hydrobicity; Thermal denaturation